Occupational exposure to welding fume in Australia: An online survey - Lin Fritschi; Timothy R. Driscoll; Ha Nguyen; Kamil Abdallah; Renee N. Carey (Elsevier, 2024)
Objective: This survey aimed to investigate exposure to welding fume in Australian workplaces and the use of protective and control measures among workers. Methods: Data were collected via a cross-sectional online survey of workers and employers involved in welding in Australia. Survey questions focused on the determinants of exposure to welding fume, welding experience and qualifications, and use of control measures. Results: There were 634 respondents to the survey across Australia of whom 577 (91%) were assessed as being exposed to welding fume, most at high levels. Welders undertook a wide range of types of welding, and higher-risk welding such as in confined and restricted spaces was common. Most workplaces did not have any form of mechanical ventilation, and use of air-supplied respiratory protection was poor even when ventilation was not used. Conclusion: Welders in Australia are exposed to several carcinogens, particularly welding fume, hexavalent chromium (CrVI) and nickel, and the use of control measures is sub-optimal. Implications for Public Health: Higher-order controls are the best way to reduce exposure to carcinogens in the workplace. The lack of use of these controls by Australian welders is concerning and needs to be a focus of attention by regulators and companies.